Motivation and marathon running - Hammer, C.; Podlog, L. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
In recent years, marathon running has become a sport for the masses. Over the past 35 years, the median finishing time for a U.S. marathon slowed by 47 min (for males), the median age for male marathoners increased from 34 (1980) to 40 years (2014), and the number of marathon finishers grew from an estimated 143,000 (1980) to over 550,000 (2014) (Running USA in 2014 Running USA annual marathon report, 2015). With slower finishing times, older participants, and dramatic increases in marathon participation rates, it is evident that marathon running has become a popular endeavor for individuals of all ages and athletic abilities. Given the appeal of marathon running, it seems worth asking the question: "why are so many individuals motivated to undertake such a grueling activity?" The issue of motivation among marathoners provides the focus of this chapter. In particular, the chapter is divided into four sections. First, as the term `motivation` has been used to refer to an array of conceptually distinct constructs, we provide a scientifically sound definition of the construct. Second, the chapter focuses on empirical research examining the issue of why individuals choose to participate in marathon training and mnning. Here the discussion centers on three main issues including: the measurement of motivation in marathon runners; participation motives for engaging in marathon training and racing; and the relationship between motives for marathon running and marathon performance. Third, we examine detrimental outcomes associated with excessive motivation for marathon training. Finally, we highlight a number of directions for future research and provide a chapter summary.